Analisis Akad Menggunakan Sistem Pembayaran Cod Pada Transaksi Online - Bachrul Ulum (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
The development of technology forces humans to always innovate, including in terms of buying and selling. Nowadays, the proliferation of internet usage has implications for new buying and selling models. One form of buying and selling that was born due to the emergence of the internet network is online buying and selling. Online buying and selling is a buying and selling activity where the seller and buyer do not have to meet to negotiate and transact and the communication used by the seller and buyer can be through communication tools such as chat, telephone, sms, Whatsapp and so on. Based on the background of the problems described above, the main problems can be identified including: How is the practice of buying and selling online with the Cash On Delivery (COD) system?, How is the fiqh muamalah review of the practice of buying and selling online with the Cash On Delivery (COD) system? The research method used in this writing is a legal research method, where normative/legal theory studies are legal studies by placing law as a construction of a system of laws and regulations and behavior. The preparation of this article uses a statutory approach, conceptual approach, and case or agreement approach. From the entire discussion of this thesis, the author can finally draw the following conclusions, In the implementation of buying and selling onilne COD (Cash On Delivery) system can be done with these steps; open the application or web from the online buying and selling platform you want, if you don't have an account then create an account first. Search for the item you want in the search field, then put the item in the shopping cart.